Penyuluhan dan Pelatihan Peningkatan Kemampuan Menjaga Kebersihan Gigi dan Mulut serta Tatalaksana ke Dokter Gigi selama Pandemi COVID-19 - Ranggaini, Dewi; Sadono, Melanie; Halim, Himawan; N Santosa, Didi (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2024)
COVID-19 cases in Indonesia have increased to require comprehensive efforts in case management and efforts to break the chain of transmission. The community in the RW. 07 Benteng Sub-district, Warudoyong District, Sukabumi City have oral health problems such as cavities, swelling of the gum, and bad breath. At the time of the COVID-19 pandemic, people are terrified to go to the dentist because of the information that dental care considers having a higher risk of COVID-19. Based on the above problems, the FKG Trisakti University’s Team provided education in counseling and training to the community in RW. 07 Sukabumi City. The case emergency, even though during the COVID-19 pandemic to get dental care, so as not to aggravate further the situation where unchecked, the swelling might interfere with breathing and endanger personal safety. they are also informed about the management to go to the dentist. To minimize the transmission of the virus such as always using a mask, carrying out the WHO standard 6-step hand washing procedure, sneezing or coughing ethics, and doing physical restrictions. While in the waiting room, also when in the practice room, the dentist and other health teams use Personal Protective Equipment (PPE), disinfection, cleaning, and handling of tools and the patient rinses his mouth with Povidone-iodine mouthwash before starting treatment. We can maintain Oral hygiene and teeth remain healthy if brushing teeth is doing appropriately, using dental floss, mouthwash from natural ingredients such as betel leaf, and avoiding foods that contain lots of sugar.